Learning tracheal intubation with a hyperangulated videolaryngoscopy blade: sub-analysis of a randomised controlled trial - Ott, Sascha; Müller-Wirtz, Lukas M.; Bustamante, Sergio; Rössler, Julian; Skubas, Nikolaos J.; Shah, Karan; Sessler, Daniel I.; Turan, Alparslan; Ruetzler, Kurt (Anaesthesia, 2024)
Introduction: The number of tracheal intubation attempts required to reach proficiency in videolaryngoscopy with hyperangulated blades is unknown. Understanding this training requirement might guide training for clinicians who perform laryngoscopy. We therefore performed a planned sub-analysis of a randomised controlled trial comparing tracheal intubation success with videolaryngoscopy vs. direct laryngoscopy to determine the number of tracheal intubations with a hyperangulated videolaryngoscope blade needed to provide an acceptable first-attempt success rate. Methods: We included clinicians from a randomised controlled trial who were familiar with direct laryngoscopy and Macintosh-blade videolaryngoscopy but inexperienced with hyperangulated videolaryngoscopy. Cumulative sum statistics were used to generate learning curves with acceptable success rates of 85% and unacceptable success rates of 70% for the primary outcome of first-attempt tracheal intubation success. Results: We included 223 clinicians (25 consultants; 35 certified registered nurse anaesthetists; 36 student registered nurse anaesthetists; 46 fellows; and 81 residents) who attempted tracheal intubation in 4312 procedures. The median (IQR [range]) number of tracheal intubations per clinician was 15 (8–25 [1–77]). First-attempt failure was low, with only 72 failed first attempts overall, and was comparable across clinician groups. In total, 133 (60%) clinicians crossed the acceptable success rate boundary while the remaining 90 (40%) clinicians crossed neither the acceptable nor unacceptable success rate boundaries. Among clinicians who crossed the acceptance boundary, the median (IQR [range]) number of attempts for learning was 12 (12–12 [12–26]). Discussion: Clinicians experienced in tracheal intubation with direct laryngoscopy but unfamiliar with hyperangulated-blade videolaryngoscopy can achieve proficiency after approximately 12 attempts.
CRIS-Team Scopus Importer:2024-12-06
Keywords: anaesthesia; laryngoscopy; learning curve; medical education; videolaryngoscopy